Gli signaling pathway modulates fibroblast activation and facilitates scar formation in pulmonary fibrosis - Tsukui, Tatsuya; Ueha, Satoshi; Shichino, Shigeyuki; Hashimoto, Shinichi; Nakajima, Takuya; Shiraishi, Kazushige; Kihara, Miho; Kiyonari, Hiroshi; Inagaki, Yutaka; Matsushima, Kouji (Biochemical and biophysical research communications, 2019)
Pulmonary fibrosis is characterized by progressive and irreversible scarring of alveoli, which causes reduction of surface epithelial area and eventually respiratory failure. The precise mechanism of alveolar scarring is poorly understood. In this study, we explored transcriptional signatures of activated fibroblasts in alveolar airspaces by using intratracheal transfer in bleomycin-induced lung fibrosis. Lung fibroblasts transferred into injured alveoli upregulated genes related to translation and metabolism in the first two days, and upregulated genes related to extracellular matrix (ECM) production between day 2 and 7. Upstream analysis of these upregulated genes suggested possible contribution of hypoxia-inducible factors 1a (Hif1a) to fibroblast activation in the first two days, and possible contribution of kruppel-like factor 4 (Klf4) and glioma-associated oncogene (Gli) transcription factors to fibroblast activation in the following profibrotic phase. Fibroblasts purified based on high Acta2 expression after intratracheal transfer were also characterized by ECM production and upstream regulation by Klf4 and Gli proteins. Pharmacological inhibition of Gli proteins by GANT61 in bleomycin-induced lung fibrosis altered the pattern of scarring characterized by dilated airspaces and smaller fibroblast clusters. Activated fibroblasts isolated from GANT61-treated mice showed decreased migration capacity, suggesting that Gli signaling inhibition attenuated fibroblast activation. In conclusion, we revealed transcriptional signatures and possible upstream regulators of activated fibroblasts in injured alveolar airspaces. The altered scar formation by Gli signaling inhibition supports that activated fibroblasts in alveolar airspaces may play a critical role in scar formation. •Hif1a is an initial gene regulator in fibroblasts exposed to injured alveolar airspaces.•Klf4 and Gli proteins may subsequently upregulate ECM genes in activated fibroblasts.•Pharmacological inhibition of Gli signalings in lung fibrosis alters scar formation.•Gli signaling inhibition reduces migration capacity of fibroblasts in fibrotic lungs.